An Interdisciplinary System for Educating Children: Hydroponics-based Smart Education System - Dinçer, Samet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In this thesis, a novel smart system based on hydroponics is proposed. It is aimed to educate children by contributing to their improvement on cognitive domain, affective domain and psychomotor domain. This hydroponics-based smart education system is task oriented, does not interfere children’s daily life and includes instant child control. It is an interdisciplinary system which consists of Android application, Raspberry Pi, Web server, MySQL server and Hydroponics system components. Self-improvement of children in terms of cognitive, affective and psychomotor could be contributed with this system’s various features. Keywords: Smart system, Mobile application, embedded system, Web, MySQL, hydroponics system, children, education, cognitive domain, affective domain, psychomotor domain.

ÖZ: Bu tezde, hidroponik temelli yeni bir akıllı sistem önerilmiştir. Bu çalışma ile çocukların bilişsel, duyuşsal ve psikomotor alanlarına katkıda bulunabilmek amaçlanmıştır. Bu hidroponik temelli akıllı eğitim sistemi görev odaklı ve çocuğun günlük yaşantısını etkilemeyecek şekilde tasarlanmıştır. Ayrıca, aile tarafından çocuk kontrolü de sağlanmaktadır. Android uygulaması, Raspberry Pi, Web sunucusu, MySQL sunucusu ve hidroponik sistem bileşenlerinden oluşan disiplinler arası bir sistemdir. Sistemde bulunan çeşitli özellikler ile çocukların kendilerini bilişsel, duyuşsal ve psikomotor alanlarında geliştirebilmesi mümkündür. Anahtar Kelimeler: Akıllı sistem, mobil uygulama, gömülü sistem, Web, MySQL, hidroponik sistem, çocuk, eğitim, bilişsel alan, duyuşsal alan, psikomotor alan.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assist. Prof. Dr. Yıltan Bitirim.
Keywords: Computer Engineering; Computational intelligence--Smart Education Systems; Education--Computer - assisted instruction; Mobile learning; Educational technology; Smart system; Mobile application; embedded system; Web; MySQL; hydroponics system; children; education; cognitive domain; affective domain; psychomotor domain